Estrogen Receptor Alpha–Expressing Neurons in Bed Nucleus of the Stria Terminalis and Hypothalamus Encoding Aggression and Mating - Wang, Wen-Qiu; Zhao, He-Xin; Shen, Xiao-Lin; Zeng, Li-Zhang; Geng, Hong-Yan (eNeuro, 2024)
Aggression and mating of male mice are strongly associated with Esr1-expressing neurons in the bed nucleus of the stria terminalis (BNSTpr) and hypothalamus in the vomeronasal pathway. By projecting to the downstream hypothalamus, the upstream BNSTpr Esr1 gates mating and aggression of male mice and maternal behavior of female mice. The medial preoptic area (MPOA) and ventrolateral subdivision of the ventromedial hypothalamus (VMHvl) are two subdivisions of the hypothalamus downstream. In addition to receiving projections from upstream BNSTpr, there is also a mutual projection between MPOA and VMHvl. In the process of transforming sex information into mating and aggression, Esr1-expressing neurons in BNSTpr, MPOA, and VMHvl act as messengers of information, finally producing inhibitory or excitatory projection. These projections are different in direction, but they all work together to control the behavior selection that is most conducive to defense and reproduction when male mice encounter female or male mice. Here, we summarized the property and the function of connections between these Esr1-expressing neurons in BNSTpr, MPOA, and VMHvl that encode mating and aggression and highlight the importance and benefits of inhibitory projection of Esr1-expressing cells in mating and aggression.